SOCIAL MASKING: The act of comfortable personalities - Yar, Lionel Jun Cheng (2018)
Social Masking is defined as conforming personalities and behaviour to suit a given person, time, place and interaction. It is a common construct found within social interaction. In a best-case scenario, social masking enables individuals to function easily within various contexts in our social world. On the contrary in a worst-case scenario, social masking serves as barriers to true acceptance, hospitality, understanding and authentic communication. As society becomes more and more progressive, the advancement of plurality has both given way to higher diversity but not necessarily higher tolerance or acceptance within those pluralities. The act of social masking has hence become more complex and harder to navigate. With a growing culture of distrust amongst people, how guarded should one be when meeting strangers for the first time? What levels of vulnerability should one adopt in any given relationship? And at what point can one be completely oneself without the fear of judgment or intolerance and the need to conform to social norms? This complex yet important social phenomenon is something I wish to investigate within my project in order to facilitate critical thought and open communication on ways to create a more inclusive, compassionate and accepting society